The Impact of Sustainable Practices on Organizational Reputation: The Mediating Role of Social Responsibility in Saudi Organizations - Arous, Jamel Ali; Alenzi, Hamoud; ElRabbat, Samar Ahmed; Hima, Nadya Ali (European Journal of Sustainable Development, 2025)
This research paper deals with a study on the relationship between sustainable practices and organizational reputation through the mediating role of social responsibility in Saudi organizations. The main purpose of the research is to contribute to understanding how sustainable practices can enhance organizational reputation. The study uses a quantitative research design, and surveys data collected from a sample of 304 administrators working in a number of Saudi organizations. The organization of literature sources and problem-solving methods indicate that the importance of this scientific problem lies in the need for an empirical examination of how sustainable practices can improve organizational reputation through the mediating effect of social responsibility. The methodological tools of the research included the use of SPSS v.23 and AMOS v.23 to test the hypotheses. The results of the empirical analysis show that sustainable practices positively affect organizational reputation, and this relationship is mediated by social responsibility. The results of the study confirm that the application of sustainable practices can enhance the organization’s reputation by enhancing its social responsibility. The results also confirm that there are no gender differences in the perception of the practices of the study variables. The results of this study can also be useful to policy makers and university administrators who seek to promote sustainable practices and enhance the organization’s reputation through effective social responsibility initiatives. Keywords: corporate social responsibility; environmental sustainability; organizational image; reputational management; sustainable business practices.